Effects of Thermal and Nonthermal Treatments on Kinetics of Mass Transfer and Selected Quality Attributes During Osmotic Dehydration of Seedless Guava (Psidium Guajava L.) - Ganjloo, Ali (2011)
This study evaluated the effect of some process parameters and selected enhancement techniques on the kinetics of mass transfer as well as selected quality attributes for osmotic dehydration of seedless guava. Experimental results revealed that higher values of solution concentration and temperature resulted in higher flows of water (39%) and solids (8%) through the seedless guava. In all cases, Peleg equation adequately (R2>0.92) described the kinetics of mass transfer during osmotic dehydration. Total color difference increased up to 21% while hardness decreased around 32% with increase process variables. A zero order kinetic model was fitted to the experimental data adequately for quality parameters (R2>0.88). The osmotic dehydration process was optimized for maximum water loss, weight reduction and minimum solute gain through response surface methodology. Results suggested optimum processing conditions of 30% w/w sucrose concentration at 33 ºC after 179 min would result in 0.15 gg-1 weight reduction, 0.2 gg-1 water loss and 0.03 gg-1 solid gain. Results showed that at the studied range of process parameters, the values of mass transfer terms were not in accordance with an efficient osmotic dehydration process in which 40–60% water loss and <10% solid gain are expected (Eren and Kaymak-Ertekin, 2007). In order to improve the rate of mass transfer a number of enhancement methods such as hot water blanching, thermosonication, ultrasound and centrifugal force were applied. The effect of hot water pretreatment at the temperature range of 80-95°C was evaluated and compared with osmotic dehydration at optimum condition. It improves the kinetics of mass transfer in terms of weight reduction, solid gain, water loss and normalized moisture content up to 15-30%, 2-6%, 16-46% and 7-20% at the temperature range of 80-90 °C, respectively. Traditional blanching lead to 17% increase and 54% decrease in total color difference and hardness values, respectively. For the first time, the simultaneous application of heat and ultrasonic wave (thermosonication) was investigated in order to reduce the intensity of heat treatments which can impair sensorial and nutritional properties of foods. Thermosonication at 90 ºC at different amplitude levels (25-75%) lead to the enhancement of mass transfer of water (up to 4%) and solid (up to 1%) during osmotic dehydration without significant (p>0.05) changes of optical and textural properties in comparison with traditional blanching. Finally, the influence of ultrasonic wave and centrifugal force as nonthermal treatment on osmotic dehydration process was investigated to overcome the drawbacks of thermal treatment. Application of ultrasonic treatment compared with osmotic dehydration at optimized condition enhanced water loss and solid gain up to 23% and 3.3%, respectively. It improved “L” value without any significant effect (p>0.05) on “a” and “b” values whereas hardness value was significantly (p<0.05) affected. Centrifugal force treatment increased water loss around 34%, however, retarded solid gain. The combination of centrifugal force with osmotic dehydration leads to decrease in hardness of samples (5%) whereas there is no significant (p<0.05) effect on color of samples.